Global Burden and Trends of Norovirus-Associated Diseases From 1990 to 2019: An Observational Trend Study - Zhang, Xiaobao; Chen, Can; Du, Yuxia; Yan, Danying; Jiang, Daixi; Liu, Xiaoxiao; Yang, Mengya; Ding, Cheng; Lan, Lei; Hecht, Robert; Yang, Shigui (Frontiers in Public Health, 2022)
Introduction: As an important pathogen causing diarrheal diseases, the burden and change of death rate of norovirus-associated diseases (NADs) globally is still unknown. Methods: Based on global disease burden data from 1990 to 2019, we analyzed the age-standardized death rate (ASDR) of NADs by age, region, country, and Socio-Demographic Index (SDI) level. The discrete Poisson model was applied in the analysis of NADs’ spatiotemporal aggregation, Joinpoint regression model to analyze the trend of death burden of NADs over 30 years and generalized linear model to identify the risk factors for the death rate from NADs. Results: The ASDR of NADs significantly decreased by a factor of approximately 2.7 times, from 5.02 (95% CI: 1.10, 11.34) in 1990 to 1.86 (95% CI: 0.36, 4.16) in 2019 (AAPC=-3.43, 95% CI: -3.56, -3.29). The death burden of NADs in 2019 was still highest in African regions despite a great decline in recent decades. However, the ASDR in high SDI countries presented an uptrend (0.12 (95% CI: 0.03, 0.26) in 1990 and 0.24 (95% CI: 0.03, 0.53) in 2019, AAPC=2.52, 95% CI: 2.02-3.03), mainly observed in the elderly over 70 years. Compared to children under 5 years, the 2019 death rate of elderly individuals over 80 years was much higher in high SDI countries. The generalized linear model showed that factors of the number of physicians (RR = 0.67), the proportions of children under 14 years (RR = 1.21), elderly individuals over 65 years (RR = 1.13), educational level (RR = 1.03) and urbanization proportion (RR = 1.01) influenced the ASDR of NADs. Conclusions: The death burden of NADs has remained high in developing regions over the last three decades and has increased among the elderly in countries with high SDI levels, even though the global trend in NAD-associated deaths has decreased significantly in the past three decades. More effective public health policies against NADs need to be implemented in high SDI regions and in the elderly.